Toxicity of Ageratum conyzoides extract against Spodoptera sp - Dian Ekawati Sari; Rahmawati Arma; Bakhtiar Bakhtiar (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2021)
Spodoptera sp. is the main pest in food crops and horticulture that can reduce production by up to 80% Control is carried out only using chemicals that can damage the environment and impact human health. so, efforts are needed for pest control by utilizing Ageratum conyzoides extracts that are more environmentally friendly. This study aims to find out the effects of A. conyzoides extract on Spodoptera sp. pests on rice plants. The study consisted of plant extraction of A. conyzoides, rearing of Spodoptera sp. and application of A. conyzoides extract on Spodoptera sp. The concentrations used are 1%, 1.5%, 2%, 2.5%, 3% and control. The results showed that the best treatment was obtained at concentrations of 3% and 2.5% with mortality percentages of 90% and 96.67%. The results of probit analysis obtained LC50 and LC90 concentrations of 1.59% and 2.53%, respectively, analysis at 72 hours after treament. Therefore, A. conizoides extract potential to be used for controlling Spodoptera sp.